(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
This essay delves into storytelling and imagination as fundamental elements of what it means to be human. Through analyses of The Man Who Mistook His Wife for a Hat by Oliver Sacks and "The Swimmer" by John Cheever, it examines how narratives shape identity, preserve meaning, and at times distort reality. By exploring the balance between creativity and truth, the work highlights both the resilience and fragility of the human spirit. For additional context, listen to the author’s reflection on the piece below.